Is There a Role for Natural Antibodies in Rejection Following Transplantation?. Issue 8 (August 2019) - Zorn, Emmanuel; See, Sarah B.
Abstract : Antibody-mediated rejection continues to hinder long-term survival of solid organ allografts. Natural antibodies (Nabs) with polyreactive and autoreactive properties have recently emerged as potential contributors to antibody-mediated graft rejection. This review discusses Nabs, their functions in health and disease, their significance in rejection following kidney, heart, and lung transplantation, and their implication in serum reactivity to key antigens associated with rejection. Finally, potential effector mechanisms of Nabs in the context of transplantation are explored.